Tolerant to air σ-alkane complexes by surface modification of single crystalline solid-state molecular organometallics using vapour-phase cationic polymerisation: SMOM@polymer - Bukvic, Alexander J; Crivoi, Dana Georgiana; Garwood, Hollie G; McKay, Alasdair I; Chen, Thomas T. D; Martínez-Martínez, Antonio J; Weller, Andrew S (Chemical communications (Cambridge, England), 2020)
Vapour-phase surface-initiated cationic polymerisation of ethylvinylether occurs at single-crystals of the σ-alkane complex [Rh(Cy 2 PCH 2 CH 2 PCy 2 )(NBA)][BAr F 4 ]. This new surface interface makes these normally very air sensitive materials tolerant to air, while also allowing for onward single-crystal to single-crystal reactivity at metal sites within the lattice. Surface-initiated cationic polymerisation of ethylvinylether at single-crystals of the σ-alkane complex [Rh(Cy 2 PCH 2 CH 2 PCy 2 )(NBA)][BAr F 4 ] imparts air-tolerance to this highly reactive complex.